Sanora Babb and the Dust Bowl - Sigmundová, Martina (Univerzita Pardubice, 2021)
This Bachelor thesis is concerned with depicting the topic of dust storms in the work of the American writer Sanora Babb. The beginning of this thesis outlines the cultural background of the United States of America in the 1930s, and puts Sanora Babb into the context. The following chapters analyze the novel Whose Names Are Unknown which analyzes the regionalist motives of Midwest and California, particularly the motives of estrangement and displacement and the forming of protests.
Sanora Babb a Dust Bowl
Keywords: Dust Bowl; farmers; migrant workers; isolation; regions; Dust Bowl; farmáři; migrující pracovníci; isolace; regiony